Hubungan Anemia pada Ibu Hamil dengan Kejadian Berat Bayi Lahir Rendah (BBLR) di Wilayah Kerja Puskesmas Cimerak Kabupaten Pangandaran - Eka Dewi Pangesti; Mia Dwi Agustiani; Novita Puspita Dewi (STIKES Columbia Asia Medan, 2025)
Low birth weight (LBW) is a major concern in Indonesia due to its impact on neonatal health and growth. One of the contributing factors is maternal anemia during pregnancy, which limits oxygen and nutrient supply to the fetus. This study aimed to determine the relationship between maternal anemia and the incidence of LBW in the working area of the Cimerak Health Center, Pangandaran Regency. This research used a retrospective case-control design involving 124 mothers, divided into 62 cases and 62 controls. The results of the chi-square test showed a significant relationship between maternal anemia and the incidence of LBW (p = 0.000). It is concluded that maternal anemia is associated with a higher risk of LBW, thus emphasizing the need for improved maternal care and anemia prevention strategies.